Singapore Case Note: Enforceability of settlement agreements - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2019)
Since the signing of the Singapore Convention on Mediation in August this year, there has been an increased interest on the enforceability of settlement agreements, particularly those arising from mediation. The case of Law Chau Loon v Alphire Group Pte Ltd [2019] SGHC 275 from the Singapore High Court provides us with some general legal principles to consider when a settlement agreement is drafted. Although mediation did not take place between the parties in dispute, the principles stated by the High Court here remain relevant to the drafting of binding mediated settlement agreements (MSAs). This case is essential reading for mediators and lawyers involved in mediations in which Singapore law may be applicable in relation to enforcement.